BENTUK PENYAJIAN TARI RENTAK BULIAN PADA ACARA PESTA PERKAWINANDI KECAMATAN BUKIT RAYA KOTA PEKANBARU PROVINSI RIAU - Lusi Febri Andesti; Desfiarini (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2025)
This research aims to reveal and describe the presentation of the Rentak Bulian dance at wedding celebrations in the Bukit Raya district of Pekanbaru City, Riau Province. The type of research is qualitative with a descriptive analytical method. The research instruments are the researcher themselves, assisted with writing tools and a camera. Data were collected through literature study, observation, interviews, and documentation. The steps for analysing the data are data collection, data reduction, data presentation, and drawing conclusions. The research results indicate that the Rentak Bulian dance at wedding celebrations in the Bukit Raya district is a new creation dance developed from healing rituals into an entertainment medium presented at wedding events, with its presentation consisting of movement, floor design, music design, dancers, props, and costumes. Gerak Tari Rentak Bulian features 7 types of movements, consisting of the Worship Movement, the Stomp Movement, the Shake Bud Movement, the Bow Movement, the Lime Mixing Movement, the Lime Sprinkling Movement, and the Four Corners Movement. The floor pattern of the Rentak Bulian Dance employs straight lines and circles. The musical instruments used to accompany the Rentak Bulian Dance include the flute, gong, tambourine, long drum, and clapper. The dancers of the Rentak Bulian Dance consist of 7 performers, including 2 strong male dancers and 5 pure and clean female dancers who have reached maturity. The properties used in the performance of the Rentak Bulian Dance are Mayang Pinang, which symbolises grandeur, a sense of responsibility, and the fortification of the elephants. Meanwhile, male costumes feature gomoh shirts, gomoh trousers, gomoh belts, gomoh headbands, and ankle janglers, while female costumes consist of kumantan blouses, kumantan skirts, pandan medical ornaments, and ankle janglers. The Rentak Bulian Dance has evolved from the sacred ritual of Bulean into a performing art. Despite undergoing transformation, this dance retains the ritual elements and the beliefs of the Bukit Raya community in supernatural powers.